A global trading system in turmoil: What is at stake for Africa? - Bouët, Antoine; Traoré, Fousseini; Laborde Debucquet, David (International Food Policy Research Institute, 2019)
The trade war between the United States and China involves the two largest players in the world economy (i.e., the two countries with the largest GDPs, and the largest exporters and importers). Consequently, increasing trade tensions between these two giants are a major stake and it is expected that these tensions will negatively affect third countries through spillover effects. Trade tensions may also become even more important and may potentially concern other players in the world economy. This is why the global trading system appears to be today in turmoil.